Analisis Pemanfaatan PLTS 80 Wp sebagai Sumber Energi Listrik pada Kapal 3 GT di Desa Tablolong Nusa Tenggara Timur - I Made Aditya Nugraha; Febi Luthfiani; Jhon Septin Mourisdo Siregar; Rasdam Rasdam; Resky Amalia Rajab (Fakultas Perikanan dan Ilmu Kelautan, Universitas Papua, 2023)
The use of fossil energy as a source of fuel to turn on generators on fishing boats has long been used to assist fishing activities in Tablolong Village. The availability and lack of good use of this energy continuously will certainly be very bad for the sustainability of the fishermen's economy and the environment. The utilization of solar energy which has such great potential in East Nusa Tenggara can be one solution. The use of this technology is in line with the Blue Economy policy by the Ministry of Marine Affairs and Fisheries Republic of Indonesia. This 80 Wp PV system is installed on a 3 GT ship, then the energy that can be generated is analyzed and the Wilcoxon test is carried out to determine the fishermen's response to the use of the PV System. The utilization of the PV System as a source of electrical energy on 3GT vessels in Tablolong Village can meet the electrical energy needs of fishing boats. The electrical energy generated can meet 189% of the ship's electricity needs of 320 Wh/day with energy that can be produced by PV of 604.04 Wh/day. This result is also supported by the Wilcoxon test of the energy produced by PV for the ship's electrical energy needs. Based on the assessment indicators that have been carried out from before and after PV installation activities on fishing boats, it was found that there was a significant difference in the electrical energy needs before and after using PV System with a significant value of 0.001 (p < 0.05).